XML Certification Quizzer. - Amoussou, Joel (XML journal :the ultimate enterprise resource.)
With the downturn in the IT industry, employers are getting hundreds of resumes for new job openings. The use of technical interviews and online assessment tools in screening job applicants is becoming very popular in the IT job market and companies offering IT skills assessment solutions are emerging in the marketplace.